2011
DOI: 10.1152/japplphysiol.00266.2011
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic preconditioning of the muscle improves maximal exercise performance but not maximal oxygen uptake in humans

Abstract: Brief episodes of nonlethal ischemia, commonly known as "ischemic preconditioning" (IP), are protective against cell injury induced by infarction. Moreover, muscle IP has been found capable of improving exercise performance. The aim of the study was the comparison of standard exercise performances carried out in normal conditions with those carried out following IP, achieved by brief muscle ischemia at rest (RIP) and after exercise (EIP). Seventeen physically active, healthy male subjects performed three incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
188
2
14

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(223 citation statements)
references
References 31 publications
19
188
2
14
Order By: Relevance
“…However, the mean difference of 0.4 km.h -1 , does not exceed our calculated typical error of 0.5 km.h -1 established during pilot across a series of similar studies under the same conditions, indicating that changes may not be meaningful. Crisafulli et al (2011) has highlighted a role for altered fatigue perception to explain enhanced performance following IP, after observing no differences in physiological parameters including V* O 2max , maximal stroke volume and maximal cardiac output. These data cannot support, or refute this, as testing occurred under different environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the mean difference of 0.4 km.h -1 , does not exceed our calculated typical error of 0.5 km.h -1 established during pilot across a series of similar studies under the same conditions, indicating that changes may not be meaningful. Crisafulli et al (2011) has highlighted a role for altered fatigue perception to explain enhanced performance following IP, after observing no differences in physiological parameters including V* O 2max , maximal stroke volume and maximal cardiac output. These data cannot support, or refute this, as testing occurred under different environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, Crisafulli et al (2011) reported a 4% increase in maximal power output and a ~40 s increase in total exercise time during an incremental cycling test to exhaustion immediately following IP, whilst de Groot et al (2010) observed a 3% increase in V0 O 2max , alongside a 1.6% increase in maximal power output during incremental cycling. Few studies have considered endurance running, however Bailey, Jones, et al (2012) reported lower blood lactate concentration (mean difference -1.07 mMol.L -1 ) throughout an incremental submaximal running test, although no subsequent effect on maximum oxygen consumption (V" O 2max ) was observed.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Ergocomp EL 1200, Marquette, Italy) for ECG data, and to a mass spectrometer (mod. II-CPX Express, Medgraphics, USA) in order to obtain metabolic and respiratory data [28]. She underwent to a cycle-ergometer incremental test (20W every 3 min,) up to volitional exhaustion, followed by 5 min of recovery.…”
Section: B) Baropodometric Evaluation Testmentioning
confidence: 99%